2020
DOI: 10.1113/ep088544
|View full text |Cite
|
Sign up to set email alerts
|

Five weeks of heat training increases haemoglobin mass in elite cyclists

Abstract: In this study we tested the hypothesis that performing 1 h of regular light exercise in a heat chamber (HEAT; 37.8 ± 0.5 • C; 65.4 ± 1.8% humidity) 5 times week −1 for a total of 5 weeks increases haemoglobin mass (Hb mass) and exercise performance in elite cyclists (V O 2 max = 76.2 ± 7.6 ml min −1 kg −1). Twenty-three male volunteers were assigned to HEAT (n = 11) or CON (n = 12; 15.5 ± 0.1 • C; 25.1 ± 0.0% humidity) training groups. Hb mass was determined before and after the intervention period in conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 50 publications
21
45
1
1
Order By: Relevance
“…Venous blood was drawn from an antecubital vein and immediately analyzed in triplicate for HbCO% with a calibrated gasometer (ABL80-Co-Ox, Radiometer, Copenhagen, Denmark). Initial duplicate measurements in our laboratory yielded a typical error (TE) of 1.8% for Hbmass, in line with previously reported values (Siebenmann et al, 2017;Rønnestad et al, 2020). The CO remaining in the system was measured with a CO meter (Monoxor Plus, Bacharach, New Kensington, USA) and subtracted from the initial amount introduced to define the exact CO bolus received with a 0.1 mL typical error.…”
Section: Total Hemoglobin Mass and Plasma Volumesupporting
confidence: 83%
“…Venous blood was drawn from an antecubital vein and immediately analyzed in triplicate for HbCO% with a calibrated gasometer (ABL80-Co-Ox, Radiometer, Copenhagen, Denmark). Initial duplicate measurements in our laboratory yielded a typical error (TE) of 1.8% for Hbmass, in line with previously reported values (Siebenmann et al, 2017;Rønnestad et al, 2020). The CO remaining in the system was measured with a CO meter (Monoxor Plus, Bacharach, New Kensington, USA) and subtracted from the initial amount introduced to define the exact CO bolus received with a 0.1 mL typical error.…”
Section: Total Hemoglobin Mass and Plasma Volumesupporting
confidence: 83%
“…Venous blood was then drawn from an antecubital vein and immediately analyzed in triplicate for carboxyhemoglobin content (HbCO%) with a calibrated gasometer (ABL80-Co-Ox, Radiometer, Copenhagen, Denmark). Initial duplicate measurements in our laboratory yielded a typical error (TE) of 1.8%, in line with previously reported values (Siebenmann et al, 2017;Rønnestad et al, 2020). The CO remaining in the system was measured with a CO meter (Monoxor Plus, Bacharach, New Kensington, USA) and subtracted from the initial amount introduced to define the exact CO bolus received with a 0.1 mL typical error.…”
Section: Methodssupporting
confidence: 90%
“…The 8% mean improvement in VO 2max observed in the current study (~ 6% more than the CON group) is comparable to the 5% observed by Lorenzo and colleagues (2010) when using a 10-day active heat acclimation protocol. Possible mechanisms facilitating this improvement in aerobic capacity with heat acclimation include a greater maximum cardiac output, as demonstrated by Lorenzo et al (2010) in their study, or increases in total haemoglobin mass, which are possible in an intervention stretching over multiple weeks, as more recently demonstrated by Rønnestad et al (2020). The iron supplements given to participants in the current study may have helped to facilitate improvements in oxygen carrying capacity, though participants were not given iron supplements by Rønnestad et al (2020) or by Scoon et al (2007), who both observed haematological adaptations following heat acclimation.…”
Section: Temperate Exercise Performancementioning
confidence: 81%